1990
DOI: 10.1042/bj2670767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenomethionine on cell growth and on S-adenosylmethionine metabolism in cultured malignant cells

Abstract: The effects of selenomethionine (SeMet) on the growth of 17 cultured cell lines were studied. SeMet in the culture medium of three hepatoma cell lines promoted cell growth at subcytotoxic levels (1-20 microM), but the growth of malignant lymphoid and myeloid cells was not stimulated. L-SeMet was cytotoxic to all 17 cell lines when assayed after culture for 3-10 days. A 50% growth inhibition was observed by 30-160 microM-SeMet in a culture medium containing 100 microM-methionine. SeMet cytotoxicity to normal (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A study of the polar reactivity of the selenonium analogue of SAM has predicted that SeAM is a competent alkylating agent (48). Accordingly, SeAM was shown to be effectively utilized in a specific enzymatic transmethylation reaction in vitro, and overall transmethylation in animal cells was not affected by the presence of SeMet (29). In this study we show that impairing the hydrolysis of SeAH in a ⌬ado1 mutant increased SeMet resistance rather than the opposite.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…A study of the polar reactivity of the selenonium analogue of SAM has predicted that SeAM is a competent alkylating agent (48). Accordingly, SeAM was shown to be effectively utilized in a specific enzymatic transmethylation reaction in vitro, and overall transmethylation in animal cells was not affected by the presence of SeMet (29). In this study we show that impairing the hydrolysis of SeAH in a ⌬ado1 mutant increased SeMet resistance rather than the opposite.…”
Section: Discussionmentioning
confidence: 60%
“…For instance, SAM is utilized by nearly a hundred methyltransferases involved in the methylation of RNA, proteins, and lipids. SAdenosylhomocysteine (SAH), the product of the transmethylation reaction, is a potent inhibitor of transferases, and its selenium-substituted counterpart could have toxic effects if it is a more effective inhibitor of the methylation reaction or a substrate with lower affinity for SAH hydrolase than the natural sulfur species (29). Lastly, a recent analysis of the metabolome of SeMet-treated S. cerevisiae cells showed a significant decrease of the reduced thiol pool coincident with increased selenylsulfides.…”
mentioning
confidence: 99%
“…1). It has been reported that the growth inhibitory effect of selenium on the tumor cell lines is attributable to a combined effect on the cell cycle and apoptosis (4,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…It may be that these substitutions affect protein turnover in a cellular context. That ratios of Se-SAM : Se-adenosylhomocysteine are decreased relative to their sulfur analogues indicates greater methylating efficiency by SeMet [63] and may be relevant to anticarcinogenesis [64], as methyltransferases play roles in gene silencing, repair of damaged proteins, activation of oncogenes and lipid metabolism. SeMet is more effective than Met as a substrate for Met-adenosyl transferase [62], forming Se-adenosyl SeMet (Se-SAM), which can serve as methyltransferase substrate in the methylation of RNA, phosphotidyl lipids, creatine, histamine and thiols.…”
Section: Methionine Mimicrymentioning
confidence: 99%